HARGA DIRI DAN INTENSI MEMBELI JERSEY SEPAK BOLA TIRUAN PADA REMAJA - SUPARNO EKO W.; GUMGUM GUMELAR; ARIF WIBISONO (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
This study aims to determine the effect of self-esteem to buying intention a fake football jersey of adolescents in Bogor city. The subject of this study is amounted to 70 respondents. The sample character of this study is adolescents aged from 15-18 years old, and the gender is man or women and football fans. The type of this study is quantitative study and the technique that researched use is non-probability purposive sampling. The researched used questionnaire technique to collect all data , the questionnaire that researched used is instrument of self-esteem, which is adapted from the Coopersmith Self-Esteem Inventory-School form and instrument of intention of buying Shukla with add three items of another buying intention, static analyst that used Based on research result, showing that there is significant influence between self-esteem against buying intention , at the R square value, the result of this study researched earned a value amounted of 0,150(15%),that means is self-esteem give influence amounted 15% against buying intention.